Analysis The Motivation Of Makam Pangeran Jayakarta Visitors As A Religious Tourism Site In Jakarta - Rizky Rivaldi Afgani; Hubertina Karolina Ngarbingan (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
In recent years, religious tourism has experienced significant growth in various regions of Indonesia. Tourists nowadays not only seeking spiritual experiences but also looking to dive into the historical aspects of the locations they visit. This study aims to analyze the potential of religious tourism at the Makam Pangeran Jayakarta, and understand the internal and external motivations as well as the experiences visiting the Makam Pangeran Jayakarta from visitors perspective. This research employs a qualitative approach, using a descriptive design. Data collection methods include observation, interviews, and documentation. Data analysis uses the SWOT model for the tourism sector developed by Yoeti. This research is expected to provide insights and information to public about the existence of religious tourism destination in the future.